Microparticle self-assembly induced by travelling surface acoustic waves. Issue 14 (11th March 2019) - Destgeer, Ghulam; Hashmi, Ali; Park, Jinsoo; Ahmed, Husnain; Afzal, Muhammad; Sung, Hyung Jin
Abstract : We present an acoustofluidic method based on travelling surface acoustic waves (TSAWs) for the self-assembly of microparticles inside a microfluidic channel. Abstract : We present an acoustofluidic method based on travelling surface acoustic waves (TSAWs) to induce self-assembly of microparticles inside a microfluidic channel. The particles are trapped above an interdigitated transducer, placed directly beneath the microchannel, by the TSAW-based direct acoustic radiation force (ARF). This approach was applied to trap 10 μm polystyrene particles, which were pushed towards the ceiling of the microchannel by 72 MHz TSAWs to form single- and multiple-layer colloidal structures. The repair of cracks and defects within the crystal lattice occurs as part of the self-assembly process. The sample flow through the first inlet can be switched with a buffer flow through the second inlet to control the number of particles assembled in the crystalline structure. The constant flow-induced Stokes drag force on the particles is balanced by the opposing TSAW-based ARF. This force balance is essential for the acoustics-based self-assembly of microparticles inside the microchannel. Moreover, we studied the effects of varying input voltage and fluid flow rate on the position and shape of the colloidal structure. The active self-assembly of microparticles into crystals with multiple layers can be used in the bottom-up fabrication of colloidal structures with dimensions greater than 500 μm × 500 μm, which is expected to have important applications in various fields.